What is emotional literacy?. (2nd April 2022) - Penfold, Sophie
Abstract : In a world where mental health is becoming more common and awareness is growing, we need to be even more mindful of our youngest members of the population; children. A term often used in professional environments is the term emotional literacy (EL) or emotional intelligence (EI), however what does this term actually mean?